Scalp Acupuncture and Treadmill Training Inhibits Neuronal Apoptosis through Activating cIAP1 in Cerebral Ischemia Rats - Qiang Tang (Hindawi Limited, 2021)
Stroke is the leading cause of long-term disability in developed countries. Multitudinous evidence suggests that treadmill training treatment is beneficial for balance and stroke rehabilitation; however, the need for stroke therapy remains unmet. In the present study, a cerebral ischemia rat model was established by permanent middle cerebral artery occlusion (pMCAO) to explore the therapeutic effect and mechanism of scalp acupuncture combined with treadmill training on ischemic stroke. Terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling and neuronal nuclear protein (NeuN) double staining and cellular inhibitor of apoptosis protein-1 (cIAP1) and NeuN immunofluorescence double staining were used to detect the short-term and long-term neuroprotective effects of scalp acupuncture combined with treadmill training on pMCAO rats. In addition, the antiapoptotic effect of the combined treatment was evaluated in pMCAO rats transfected with cIAP1 shRNA. Western blotting was used to detect the relative protein expression in the caspase-8/-9/-3 activation pathway downstream of cIAP1 to further clarify its regulatory mechanism. Our results showed that scalp acupuncture combined with treadmill training successfully achieved short-term and long-term functional improvement within 14 days after stroke, significantly inhibited neuronal apoptosis, and upregulated the expression of cIAP1 protein in the ischemic penumbra area of the ischemic brain. However, no significant functional improvement and antiapoptotic effect were found in pMCAO rats transfected with cIAP1 shRNA. Western blotting results showed that the combined therapy markedly inhibited the activation of the caspase-8/-9/-3 pathway. These findings indicate that scalp acupuncture combined with treadmill training therapy may serve as a more effective alternative modality in the treatment of ischemic stroke, playing an antiapoptotic role by upregulating the expression of cIAP1 and inhibiting the activation of the caspase-8/-9/-3 pathway.